Miscarriages of Justice in Australia: Unfinished Business (Global Journal of Management and Business Research, 2021)
No system of criminal justice is perfect. Some are more imperfect than others. The imperfections may arise from the wrongs of tyrannical rulers. During such regimes, the judges may become brutal in the extreme. The chances of securing justice from such judges will be remote. Yet even in jurisdictions which pride themselves on the independence and incorruptibility of their judges may sometimes adopt crimes, or follow practices, that seriously impede the conduct of a trial and lead to unjust and wrongful outcomes. Australia#x2019;s procedures of criminal justice were mostly inherited from England. This was the case in most of the other colonies of the British Crown. In fact, it is unlikely that the British settlements in Australia, would have been chosen as penal colonies, but for a crisis at the time in the English criminal justice system. Following the American Revolution of 1776-83, it became necessity for Britain to find an alternative place to which convicted prisoners could be sent, after the American settlements secured their independence. Once that happened, the Americans refused to accept more English convicts, preferring the free labour of unpaid slaves to boatloads of low class English prisoners. Even the humblest of these carried with them the residual entitlements of the common law of England, a fact that sometimes made them troublesome.